Anti-Inflammatory and Antiapoptotic Responses to Infection: A Common Denominator of Human and Bovine Macrophages Infected with Mycobacterium avium Subsp. paratuberculosis. (20th January 2013) - Abendaño, Naiara; Juste, Ramon A.; Alonso-Hearn, Marta
Abstract : Mycobacterium avium subsp. paratuberculosis ( Map ) is the causative agent of a chronic intestinal inflammation in ruminants named Johne's disease or paratuberculosis and a possible etiopathological agent of human Crohn's disease (CD). Analysis of macrophage transcriptomes in response to Map infection is expected to provide key missing information in the understanding of the role of this pathogen in establishing an inappropriate and persistent infection in a susceptible host and of the molecular mechanisms that might underlie the early phases of CD. In this paper we summarize transcriptomic studies of human and bovine peripheral blood mononuclear cells (PBMC), monocyte-derived macrophages (MDMs), and macrophages-like cell lines in vitro infected with Map . Most studies included in this paper consistently reported common gene expression signatures of bovine and human macrophages in response to Map such as enhanced expression of the anti-inflammatory cytokines IL-10 and IL-6, which promote bacterial survival. Overexpression of IL-10 could be responsible for the Map -associated reduction in the expression of the proapoptotic TNF- α gene observed in bovine and human macrophages.